2011
DOI: 10.1111/j.1478-3231.2011.02481.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between occult hepatitis B infection and the risk of hepatocellular carcinoma: a meta‐analysis

Abstract: Our findings suggest that occult HBV infection was associated with an increased risk of HCC. Occult HBV may serve as a cofactor in the development of HCV-related HCC, and it may also play a direct role in promoting Non-B and Non-C HCC growth. Suggestive evidence indicates that individuals with a concomitant presence of anti-HBs and anti-HBc had an increased risk of occult HBV infection. However, further studies are needed to clarify these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 33 publications
6
105
2
5
Order By: Relevance
“…In contrast, all HBV DNA-positive cases in the HCV group were positive for anti-HBc, and more than half were positive for anti-HBs. This result is in accordance with the fi nding that OBI is more prevalent in seropositive patients who are positive for anti-HBc and/or anti-HBs (23) (29) (37) (42) (43) . The occurrence of occult infection despite the presence of neutralizing an ti-HBs can result from mutations affecting the S region of the HBV genome (39) .…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, all HBV DNA-positive cases in the HCV group were positive for anti-HBc, and more than half were positive for anti-HBs. This result is in accordance with the fi nding that OBI is more prevalent in seropositive patients who are positive for anti-HBc and/or anti-HBs (23) (29) (37) (42) (43) . The occurrence of occult infection despite the presence of neutralizing an ti-HBs can result from mutations affecting the S region of the HBV genome (39) .…”
Section: Discussionsupporting
confidence: 80%
“…Many studies confirm a relatively high frequency of occult hepatitis B viral infection in hemodialysed patients [2] [19] Hepatocellular carcinoma (HCC) [20] No case of HCC was noted in our study on condition of the anatomo-pathologic test which was not carried out in our patients. The occult hepatitis B viral infection prevalence varies from 10% -60% and even more in case of HCC with unknown aetiology [1].…”
Section: Occult Hepatitis B Viral Infection In Hemodialysed Patientsmentioning
confidence: 75%
“…Th ese authors found that 2.07% of blood donors had Anti-HBc total alone 25 . Shi et al suggested that occult HBV infection was associated with an increased risk of hepatocellular carcinoma 26 .…”
Section: Confl Ict Of Interest Disclosurementioning
confidence: 99%